Frances G. Wickes Foundation records - Frances G. Wickes Foundation
Correspondence, minutes of meetings, corporate records, annual reports, financial material, a file on the management of the estate of Frances G. Wickes, and other records pertaining primarily to the support of institutions and projects related to the Jungian school of analytical psychology. Includes material concerning the estate of the writer Mary Louise Parmalee Peebles. Correspondents include William McGuire and Muriel Rukeyser.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division's Recorded Sound Section.
Foundation formed by the estate of Frances G. Wickes for the financial support of charitable endeavors in Jungian analytical psychology and other scientific, literary, or educational fields.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: McGuire, William, -- 1917- -- Correspondence; Peebles, Mary Louise Parmelee, -- 1833-1915 -- Estate; Rukeyser, Muriel, -- 1913-1980 -- Correspondence; Wickes, Frances G. -- 1875-1967 -- Estate; Jungian psychology; Psychoanalysis